Profil Pranata Sosial Komunitas Suku Nuaulu: (Studi Kehidupan Sosial Budaya Masyarakat Negeri Nua Nea Maluku Tengah) - Manuputty, Anike J. M.; Nahuway, Lodewyk (Public Policy, 2021)
ABSTRACT Social institutions are rules that apply in regulating human behavior in acting based on considerations of norms and values ​​that live in the life of society. This study aims to determine the existence and benefits of socio-cultural institutions in the Nuaulu tribe community. Data collection techniques with observation and in-depth interviews. Research informants came from elements of the state government, traditional leaders, youth leaders, educators and community leaders. The results of the data analysis concluded that hereditary customs strongly influenced the life of the Nuaulu people with the loyalty of the people in carrying out the prevailing institutions. The economic system and the community's livelihood system are farming, processing sago, gathering and laboring. The socio-cultural institutional arrangements are in the form of an adult ceremony for boys (Brokeneri), an adult ceremony for girls (pinamou), a wedding ceremony, a pregnancy ceremony, a birth ceremony, a haircut ceremony (tihtikuau) and a funeral ceremony. The structure of the kinship system is a patrilineal (male lineage) and it is not required to have intermarriage. Religious institutions and beliefs are tribal religions. Educational institutions, knowledge, and technology are based on experience (local knowledge) from generation to generation, and children of school age have attended various levels of education to tertiary education. Keywords: Social Institutions, Nuaulu Tribe Community.